Officer-involved shootings: testing the effect of question timing on memory accuracy for stressful events - Porter, Louise E. (Journal of experimental criminology, 2019)
This randomised controlled trial tested the effect of immediate versus delayed, as well as repeated, questioning on memory retrieval regarding details of officer-involved shootings.